PENGARUH STORE IMAGE, ONLINE CUSTOMER REVIEW, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE DI SURABAYA - Sufyan Mulyana; Diah Ayu Sanggarwati; Agung Dwi Nugroho (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
The rapid development of technology and information in the current era of globalization is causing a significant shift in human behavior, particularly in the area of shopping. With the growing presence of the internet, people now prefer to make online transactions due to its practicality and time-saving benefits. In this study, the aim is to examine the influence of store image, online customer reviews, and promotions on purchasing decisions in the Shopee marketplace in Surabaya. A quantitative approach was employed, using questionnaires to gather data. The sampling technique used was purposive sampling, where a specific number of respondents were randomly selected based on certain criteria. A total of 96 respondents were included in the sample. The data was analyzed using multiple linear regression analysis and processed using SPSS 21 software. After testing the proposed hypotheses, the results of the study indicate that the variables of store image (X1), online customer reviews (X2), and promotions (X3) have a positive and significant impact on purchasing decisions (Y), both individually and collectively.